2014
DOI: 10.1162/rest_a_00357
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Spillovers from Research Universities: Evidence from Endowment Value Shocks

Abstract: We estimate the local spillovers from research university activity in a sample of urban counties. We use the fact that universities tend to follow a rigid endowment spending policy based on the market value of their endowments to identify the causal effect of university activity on labor income in the non-education sector. Our instrument for university expenditures is based on the interaction between each university's lagged endowment level and the variation in stock market shocks over time. We find statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
90
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 58 publications
(38 reference statements)
7
90
0
2
Order By: Relevance
“…Thus it has been difficult to capture the human dimension of the impact of research on the economy. What little evidence there is has been based on an analysis of patent clusters (2) (3), the geographic and industry placement of new PhDs (4)(5)(6), or on bibliometric approaches linking grants, patents and publications (7)(8). One noteworthy exception has been expensive - the United Kingdom spent over £34 million in explicit costs, and much more in implicit costs, to generate almost 7,000 case studies.…”
mentioning
confidence: 99%
“…Thus it has been difficult to capture the human dimension of the impact of research on the economy. What little evidence there is has been based on an analysis of patent clusters (2) (3), the geographic and industry placement of new PhDs (4)(5)(6), or on bibliometric approaches linking grants, patents and publications (7)(8). One noteworthy exception has been expensive - the United Kingdom spent over £34 million in explicit costs, and much more in implicit costs, to generate almost 7,000 case studies.…”
mentioning
confidence: 99%
“…Based on data from the National Science Foundation, we further construct a state-level knowledge intensity variable reflecting state industry-financed R&D expenditure at research intensive (doctoral granting) universities (INDUSTRY_FINANCED_RND). Prior research considers research universities as one important source of innovative knowledge and skilled labor for private enterprises in the area (e.g., see Zucker et al (1998), and Kantor and Whalley (2014)). Industry-financed R&D expenditure at local research intensive universities reflects the reliance of local industries on research institutes as a source of knowledge creation and innovation.…”
Section: Industry State and Economic Conditionsmentioning
confidence: 99%
“…This result suggests that, as local industries in those states depend heavily on research universities as a source for innovative knowledge and skilled labor (see, e.g., Zucker, Darby, and Brewer (1998) and Kantor and Whalley (2014)), the rejection of the previously adopted IDD makes it easier for local industries to recruit employees with valuable knowledge from local research universities, which helps mitigate the negative impact of IDD rejection on shareholder value.…”
Section: Introductionmentioning
confidence: 99%
“…However, much of the literature has been based on aggregate data with links inferred rather than directly measured (Hausman 2012;Kantor & Whalley 2014;Saha et al 2015). This paper uses extremely granular data about purchases made in the process of conducting research to directly examine the links between universities and businesses in three countries (France, Spain and the United States).…”
Section: Introductionmentioning
confidence: 99%
“…Part of the effect could be due to the effects of educational investments. Although it has been difficult to identify these relationships, work in Sweden has shown that universities have important effects on the productivity of workers (Andersson et al 2004) and work in the United States suggests that a 10% increase in higher education spending increases local non-education sector labor income by about 0.5% (Kantor & Whalley 2014).…”
Section: Introductionmentioning
confidence: 99%